2020
DOI: 10.1121/10.0000646
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced amplitude modulations contribute to the Lombard intelligibility benefit: Evidence from the Nijmegen Corpus of Lombard Speech

Abstract: Speakers adjust their voice when talking in noise, which is known as Lombard speech. These acoustic adjustments facilitate speech comprehension in noise relative to plain speech (i.e., speech produced in quiet). However, exactly which characteristics of Lombard speech drive this intelligibility benefit in noise remains unclear. This study assessed the contribution of enhanced amplitude modulations to the Lombard speech intelligibility benefit by demonstrating that (1) native speakers of Dutch in the Nijmegen C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…As expected, and in line with previous studies [ 3 , 5 , 23 , 57 ], it was confirmed that the lists recorded under the Lombard effect are more intelligible than the lists recorded in silence, maintaining greater discrimination as SNR decreases and greater intelligibility when presented in the same SNR conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, and in line with previous studies [ 3 , 5 , 23 , 57 ], it was confirmed that the lists recorded under the Lombard effect are more intelligible than the lists recorded in silence, maintaining greater discrimination as SNR decreases and greater intelligibility when presented in the same SNR conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In Junqua [ 16 ], significant differences were also found between male and female speakers, with Lombard speech by females being more intelligible. This set of features makes speech produced under the Lombard effect more intelligible than speech produced in silence when presented under equal SNR conditions [ 3 , 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our proposed TTS speech was shorter than human speech, perhaps due to the speaking rate difference between the speech in WSJ training materials and our natural Lombard speech data. In natural speech, the Lombard effect is not simply a temporal envelope expansion from normal speech and it produce more pronounced amplitude modulations in noise [49], which is not limited to intensity, pitch, and duration enhancement. This might also be the reason for the performance difference between human and TTS speech, since our TTS was trained using Lombard speech with a focus on prosody improvement.…”
Section: B Non-incremental Tts In Static Noise Conditionsmentioning
confidence: 99%
“…In the original study about the speech-in-noise data set B (Bosker & Cooke, 2020; Experiment 2), the authors reported that speech produced in noise (Lombard speech) was more intelligible in noise-measured in human PWC scores-when compared to speech produced in quiet (plain speech), even when played at the same SNR. This phenomenon, known as the Lombard speech intelligibility benefit in noise, was first discovered by Dreher and O'Neill (1957) and has been replicated in a large body of literature ever since (Chung et al, 2005;Junqua, 1993;Lu & Cooke, 2008; Pittman & Wiley, Summers et al, 1988).…”
Section: Tsr Shows Best Relation To Acoustic Predictors Of Intelligibmentioning
confidence: 99%